ANALISIS KESALAHAN STRUKTUR DAN PEMAKAIAN BAHASA INDONESIA PADA TEKS PERSUASI KARANGAN SISWA KELAS 8 SMP DI SURAKARTA - Nesa Amelia Subekti; Sumarwati Sumarwati; Raheni Suhita (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The results shows that there are structure error and Indonesian language usage error on the persuasion text written by students at grade 8 of Junior High School in Surakarta. Those errors on the incomplete structure of persuasion text especially in the reaffirmation section. The Indonesian language usage errors include spelling error, diction error, and grammatical error. The most common errors of spelling comprises capital letters and punctuation marks usage particularly full stop and comma. The most-found errors of diction comprises improper diction selection and nonstandard diction. Grammatical error is mainly caused by ineffective sentence. Those errors are caused by some factors. The factors are (1) students do not understand the structure of persuasion text, (2) students have lack of spelling and diction knowledge, (3) the lack of examples given by teacher, (4) the lack of writing practice, and (5) student lack motivation within writing.